Formulation And Physical Evaluation Of Face Mist Containing Cucumber (Cucumis sativus L.) Extract As a Facial Moisturizer - Putri, Elsa Claudia; Dwiningrum, Riza; Pratiwi, Mida; Safutri, Wina (LPPM Universitas Dhyana Pura, 2025)
Face mist is a skin-refreshing product that primarily functions to hydrate the facial skin and is effective in maintaining skin moisture, as well as preventing skin damage caused by free radicals from air pollution. One plant known as a source of antioxidants is cucumber (Cucumis sativus L.), which contains antioxidants, vitamins, minerals, and phytochemical compounds such as flavonoids, terpenoids, and saponins that nourish and help retain skin moisture.This study aims to determine the optimal concentration of cucumber extract in a face mist formulation that provides the best moisturizing effect on facial skin. The research employed an experimental method by formulating cucumber extract face mist, followed by evaluation of its physical properties, including organoleptic test, homogeneity test, pH test, specific gravity test, spray dispersion test, spray condition test, drying time test, protection ability test, stability test, preference test, and moisturizing test.Results indicated that cucumber extract contains flavonoids, saponins, and terpenoids with potential moisturizing properties. The face mist formulations with concentrations F0 (0%), F1 (1%), F2 (3%), and F3 (5%) demonstrated good physical stability both before and after the stability test over the designated time period. F0 (0%) and F1 (1%) were the most preferred by panelists for colour and absorption properties, while F1 (1%) was the most preferred in terms of aroma. In the moisturizing test, the increase in skin moisture levels before and after treatment were F0: 10.6%, F1: 10.2%, F2: 10.9%, and F3: 11.3%. The conclusion of this study is that the best results were obtained at concentrations F5 and F1 which provided stable physical properties and a good level of panellist preference, so that this face mist preparation has he the potential to be used as a natural facial moisturizer.